Integration of Science at Islamic Universities in Indonesia: Delving Lecturers’ Perception - Muhammad Yafiz; Aqwa Naser Daulay (STAI Hubbulwathan Duri, 2023)
In the application of the concept of scientific integration, there are still hurdles in changing the learning curriculum and lecturers' understanding of Islam and science. Therefore, this study intends to examine the perspectives of lecturers at Islamic universities in Indonesia about the concept and implementation of science integration. This descriptive study employs three data-gathering methods, namely a literature review, in-depth interviews, and perception surveys using a two-tier system. 73 lecturers from the Faculties of Islamic Business Economy were recruited as participants. According to the findings of the analysis, the concept and implementation of science integration depend on the lecturers’ Islamic insight, where at the time of implementation 97.5% of lecturers answered that they believed they could teach the subjects. Moreover, the teaching contains Islamic issues with an Islamic scientific orientation; 76% of lecturers argue that as long as lecturers have attended training, seminars, workshops, and articles that review the integration of science according to the themes discussed. Furthermore, this research shows that the integration of science understood and implemented by lecturers is based on a dialogical approach that views the human relationship with God as a source of knowledge, which is a form of view and understanding of science that is open and respects knowledge types that exist proportionally and considerations as academics and Muslims.